Application of technology in food industry / Baderisang Mohamed, Mohd. Sukor Md. Yusoff and Siti Nur Athirah Mohd Kamal - Mohamed, Baderisang; Md. Yusoff, Mohd. Sukor; Mohd Kamal, Siti Nur Athirah (Faculty of Business and Management, Universiti Teknologi MARA Cawangan Kedah, 2022)
When it comes to cooking and eating, technology is unnecessarily the first thing that springs to mind. On the other hand, technology has changed the way we create and find food over time because of applications, robotics, data, and data processing techniques, among other things. Technology helps food companies produce more effectively to meet the demands of a growing global population. Given that there are currently 7.5 billion people on the planet, it follows that the need for food is increasing on an annual basis (Martin, 2019). It is possible to increase the shelf life and safety of food by applying technology to improve the processing and packaging of the product. In the food sector, automation improves quality while also reducing costs for the company. The use of robotics lowers the cost of food preservation while simultaneously increasing the amount of food produced. It is estimated that over 30,000 robots work in the European food business, with the number of robots per 10,000 workers increasing from 62 in 2013 to 84 in 2017 (Adamo Software, 2020). Not only do countries such as Sweden, Denmark, the Netherlands, and Italy, have a large market, but also the highest robot densities. Robotic equipment can aid in reducing safety issues in the food industry's more dangerous tasks, which are becoming increasingly common. Precision agriculture is important when it comes to determining how technology may be used to benefit farmers. GPS tracking devices and satellite photos are being used to monitor agricultural production, soil levels, and weather patterns to increase farm efficiency (Marketing Tutor, 2019). These technologies do not only see what is going on in the fields, but they may also use the results of the analysis to determine the health of the soil and the crop's yield. Drones are one of the most important devices farmers are using to accomplish this. They can locate and detect ill or damaged crops and they may also provide urgent treatment. The implementation of these drones does not eliminate the need for labourers but aids them to become more efficient in their work through increased productivity. With strict product standards in vast quantities, as well as a need to reduce costs, robotic elements assist in establishing a faster environment that produces more goods than what would be possible with traditional labour (Marketing Tutor, n.d.).